Happily Unhelpful: Infants’ Everyday Helping and its Connections to Early Prosocial Development - Hammond, Stuart I.; Brownell, Celia A. (Frontiers in Psychology, 2018)
Young children’s everyday helping in the home has received relatively little attention in research on prosocial behavior. Nevertheless, key features such as young children’s cheerful participation in chores around the home, including in ways that make accomplishing these chores more difficult for parents, can reveal important facets of early prosocial development. The present study reports the results of an Internet (MTurk) survey of over 500 families with children aged 1 to 4 years about their children’s prosocial tendencies, participation in nine common chores, whether children’s helping attempts were helpful or not, and attributions about children’s motives for helping. Consistent with much prior research, parents reported that children became more prosocial with age. The majority of parents reported children’s participation in everyday helping is at times unhelpful. Parents attributed children’s helping to a variety of motives and these, too, changed with age. Fathers had somewhat different perceptions of children’s everyday helping than mothers. Results are discussed in terms of how understanding everyday helping can contribute to ongoing debates in the literature about the roots of prosocial behavior.